PENERAPAN KONSEP BANGUNAN NOL SAMPAH PADA DESAIN FASILITAS PENGOLAHAN SAMPAH DI MUARA ANGKE - Alvin Pranata; Stephanus Huwae (Jurusan Arsitektur dan Perencanaan, 2021)
One of the ecological problems in Indonesia is waste. In dealing with these problems, adequate processing facilities are needed, as well as human awareness to reduce waste. Waste processing can be done by recycling it into useful goods, converting waste into a source of electrical energy, or into organic fertilizer by implementing a zero waste or